Model Pembelajaran Seni di Sekolah Dasar: Systematic Literature Review 2020-2025 - Fitriyani Fitriyani; Deni Setiawan; Eka Titi Andaryani (STKIP Subang, 2025)
The learning models used by teachers in arts education at the elementary school level are still not very varied. This condition indicates the need for a deeper understanding of various art learning models. This study aims to examine the novelty and findings related to trends in art learning models in elementary schools from 2020 to 2025. The research method employed was a Systematic Literature Review (SLR) using the PRISMA model, which includes the stages of identification, screening, eligibility, and verification. Article searches were conducted using the Publish or Perish application with the keywords “model,” “art,” and “elementary school” for the period 2020–2025. An initial search yielded 500 articles, which were then screened and narrowed down to 26 relevant articles for analysis. The results indicate that trends in art learning models in elementary schools during 2020–2025 were dominated by the Project-Based Learning model, classroom action research, visual arts materials, and studies conducted in Grades IV and V. However, limitations were identified in quantitative research, studies involving Grade VI, music and dance art materials, as well as integration with local culture, the Projek Penguatan Profil Pelajar Pancasila (P5), and digital media. Based on these findings, it can be concluded that there are opportunities to develop and investigate more diverse, innovative, integrated, and student-oriented art learning models in elementary schools.